Genetic determinants of telomere length and risk of pancreatic cancer: A PANDoRA study - Campa, Daniele; Matarazzi, Martina; Greenhalf, William; Bijlsma, Maarten; Saum, Kai‐Uwe; Pasquali, Claudio; Laarhoven, Hanneke; Szentesi, Andrea; Federici, Francesca; Vodicka, Pavel; Funel, Niccola; Pezzilli, Raffaele; et al. (International journal of cancer, 2019)
Telomere deregulation is a hallmark of cancer. Telomere length measured in lymphocytes (LTL) has been shown to be a risk marker for several cancers. For pancreatic ductal adenocarcinoma (PDAC) consensus is lacking whether risk is associated with long or short telomeres. Mendelian randomization approaches have shown that a score built from SNPs associated with LTL could be used as a robust risk marker. We explored this approach in a large scale study within the PANcreatic Disease ReseArch (PANDoRA) consortium. We analyzed 10 SNPs (ZNF676‐rs409627, TERT‐rs2736100, CTC1‐rs3027234, DHX35‐rs6028466, PXK‐rs6772228, NAF1‐rs7675998, ZNF208‐rs8105767, OBFC1‐rs9420907, ACYP2‐rs11125529 and TERC‐rs10936599) alone and combined in a LTL genetic score (“teloscore”, which explains 2.2% of the telomere variability) in relation to PDAC risk in 2,374 cases and 4,326 controls. We identified several associations with PDAC risk, among which the strongest were with the TERT‐rs2736100 SNP (OR = 1.54; 95%CI 1.35–1.76; p = 1.54 × 10−10) and a novel one with the NAF1‐rs7675998 SNP (OR = 0.80; 95%CI 0.73–0.88; p = 1.87 × 10−6, ptrend = 3.27 × 10−7). The association of short LTL, measured by the teloscore, with PDAC risk reached genome‐wide significance (p = 2.98 × 10−9 for highest vs. lowest quintile; p = 1.82 × 10−10 as a continuous variable). In conclusion, we present a novel genome‐wide candidate SNP for PDAC risk (TERT‐rs2736100), a completely new signal (NAF1‐rs7675998) approaching genome‐wide significance and we report a strong association between the teloscore and risk of pancreatic cancer, suggesting that telomeres are a potential risk factor for pancreatic cancer. What's new? How does lymphocyte telomere length affect pancreatic cancer risk? These authors analyzed 10 SNPs associated with telomere length and their relationship with pancreatic cancer risk, using data from the Pancreatic Disease Research (PANDoRA) consortium. Each patient received a “teloscore” based on the combined SNP data, and it turned out that a low teloscore ‐ predicting a short telomere ‐ was associated with increased pancreatic cancer risk. The researchers also identified for the first time a significant genome‐wide association between a SNP, TERT‐rs2736100, and increased pancreatic cancer risk. They also discovered a completely novel association between a SNP, NAF1‐rs7675998, and decreased risk.